EU Policy-Making on GMOs - Kritikos, Mihalis. author. aut Link
XV, 341 p.
Keywords: ‘A critical analysis of the complex scientific, legal, and ethical challenges faced by the decision-making bodies of the European Union in governing the planting of GM crops. It is a fascinating case-study of the politics of risk management in Europe.’ —David Vogel, University of California, Berkeley, USA ‘This book will command the attention of policy-makers and academics not just in this field but of that of wider EU risk regulation. It is a must-read.’ —Damian Chalmers, the National University of Singapore and the London School of Economics and Political Science, UK ‘A masterful analysis of how existing institutions shape the regulation of new technologies.’ —Calestous Juma, Harvard University, USA This book examines the development and implementation of the EU’s legislative framework on the commercial release of GMO products as a case study of social regulation operating within a predominantly technical framework. The analysis and findings are based on an extensive documentary analysis and interviews with regulators, risk assessors, public interest groups and biotechnology experts. It argues that in the case of the EU biotechnology framework, the particular institutional settings created for the formulation and interpretation of its provisions have been of decisive importance in elaborating a proceduralised ‘science-based’ prior authorization scheme as the preferred framework for granting commercial permits. This interdisciplinary work will appeal to EU lawyers, decision-makers and risk managers as well as academics working in the fields of EU studies, politics, law, risk governance, sociology of science/risk and technology assessment. Mihalis Kritikos is Research Fellow at the Law, Science, Technology and Society research group at the Faculty of Law and Criminology, and Associate Researcher at the Institute of European Studies, Vrije Universiteit Brussels (VUB), Belgium, and a Fellow at Athens Public International Law Center (PIL), Greece. This book is based on a PhD thesis that was awarded the 2008 UACES Prize for Best Thesis in European Studies in Europe and with the EPEES 1st Prize for Best Thesis by a Greek Researcher (2004-2008).